Antibacterial Activity Ods Fractions Of Marine Sponge Auletta sp. Against Mycobacterium smegmatis - Deiske A. Sumilat (Sam Ratulangi University, 2019)
The marine sponge collected from tropical coral reefs in Manado North Sulawesi Indonesia was screened for antimicrobial activities. In the screening program to search for antituberculotic inhibitors, the result found that the ethanol extract ODS fractions 4 – 6 with concentration 5 mg/mL of an Indonesian marine sponge Auletta sp. was exhibited inhibitory activity against nonpathogenic Mycobacterium smegmatis at concentration 10, 20, 30µg/disc each fraction respectively. Fractions 4 - 5 with concentration 10µg/disc were most active, the inhibition zone 11, 12 mm, respectively.Keywords: marine sponge, antimicrobial, antituberculosis, Mycobacterium smegmatis